Use of Information and Communication Technology in Agricultural Extension - Lusiana Andriani; All Rizky Ramadhan; Anugerah Zebua; Agung Kurniawan Sastro (Journal Analytica Islamica, 2023)
This research was conducted to describe the use of information and communication technology in agricultural extension. The method used is qualitative research using library research techniques. Qualitative research is a research method that focuses on scientific research activities by describing and understanding the social phenomena that are observed. The library study research technique is a series of scientific activities carried out by collecting a number of information that is relevant to the topic or problem that will be or is being studied with the literature as the main source of reference. Researchers carried out library study data collection techniques regarding the use of information and communication technology in agricultural extension through scientific articles, journals, books, etc. The data analysis technique used in qualitative analysis has four stages, namely data collection, data reduction, data presentation and conclusion drawing and verification. The use of information and communication technology in agricultural extension is important to make it easier for instructors to convey information, and farmers can easily access information about agriculture. Apart from that, the use of ICT can be done in various ways, such as using mass media, online media and the internet. From several existing studies, farmers and agricultural extension workers use the internet and online media such as social media for extension activities. Apart from providing farmers with the impact of increasing knowledge from this information, farmers also get an indirect impact, namely increasing the production of their agricultural products. Farmers can also utilize information and communication technology for the purpose of selling their agricultural products and various other needs.